STUDI PEMETAAN PERSEPSI KONSUMEN ATAS OPERATOR CDMA FIXED WIRELESS ACCESS - -, Zulganef; Zumara, Yuri Fathia (Jurnal Manajemen dan Keuangan, 2008)
Positioning is one of the most important strategies in Marketing. However, there are not so many companies which are investigate the positioning of their product(s). This research investigated the positioning of three CDMA operators in Jakarta. This research conducted through two steps investigation. First, we investigated some modal salient believes that evaluated by consumer, and then, based on the modal salient believes, we mapped the perception of consumers on CDMA operators products. To explore the modal salient believes we used factor analysis technique, while to mapping the perception of consumers on CDMA products we used multidimensional scaling technique. In the first step we obtained 8 factors, while in the second step we found that only âesiaâ which perceived by consumer is similar to company operator seeking. The others (flexi and star one) are not perceived similar to operator seeking. Sample size 150 respondent for first step, and 100 respondent for the second. This paper also discussed results of the research and made some recommendations.Keywords: Telecommunication, CDMA, Factor Analysis, Multidimensional Scaling, and Positioning.